Interaction between Fiscal and Monetary Policies: Directions of Causality in Case of Jordan 1990-2011 (Global Journal of Management and Business Research, 2015)
This paper is an effort to explore the interaction between fiscal and monetary policies in Jordan through investigating the short-term and long-term relationship between government expenditure as a fiscal policy, money supply as a monetary policy, and inflation as a result and cause of these policies. Using annual data for the period 1990-2011, the study applies cointegration test, Granger-causality, and VECM techniques to inspect the long-term and shortterm relationship and the directions of causality, also the speed of adjustment toward long-term equilibrium between the variables.
Keywords: fiscal policy; monetary policy; government expenditure; money supply; inflation; granger-causality; co-integration; jordan